The Effect of Semantic and Discourse Features on the Use of Null and Overt Subjects - A Quantitative Study of Third Person Subjects in Brazilian Portuguese - Soares,Eduardo Correa (2020)
ABSTRACT In a corpus study and two acceptability experiments, we investigate whether semantic and discourse features of the antecedents affect the use of null and overt subjects in Brazilian Portuguese. Previous literature has proposed two hypotheses: the Hierarchy of Referentiality Hypothesis (Cyrino et al. 2000, inter alia) and the Semantic Gender Hypothesis (Creus & Menuzzi 2004, among others). We show that animacy and specificity affect the relative frequency of null and overt subjects and their acceptability in sentences. We propose an approach that accounts for previously published results as well as our new data in the light of a theory of anaphora resolution (Ariel 1990, etc).